THE EFFECTIVENESS OF QUESTION-ANSWER RELATIONSHIP AND ANTICIPATION-REACTION GUIDE STRATEGIES FOR TEACHING READING HORTATORY EXPOSITION TEXTS TO STUDENTS WITH HIGH AND LOW CRITICAL THINKING - Haris Hamdani (Universitas Wiralodra, 2021)
This study investigates the effectiveness of Question-Answer Relationship and Anticipation-Reaction Guide strategies for enhancing students’ reading comprehension to students with high and low critical thinking. This study is quantitative research by using experimental factorial design 2x2. The participants of this study were 26 students of XI-IPS1 as the first experimental group and 25 students of XI-IPS 2 as the second experimental group at the Islamic Private Senior High School Sultan Agung 3 Semarang. The findings of this study show that (1) Question-Answer Relationship strategy has better effect for students with high and low critical thinking (2) Question-Answer Relationship and Anticipation-Reaction Guide strategies are equal treated to students with high critical thinking (3) Question-Answer Relationship strategy has better effect to students with low critical thinking (4) the students with high and low critical thinking improve equally treated by Question-Answer Relationship strategy (5) the students with high critical thinking improve better treated by Anticipation-Reaction Guide strategy (6) there is an interaction among teaching strategies, reading comprehension, and their critical thinking. To sum up, there is an interaction among teaching strategies, reading comprehension, and students’ critical thinking in teaching reading hortatory exposition texts to students with high and low critical thinking. Keywords: Anticipation-Reaction Guide, High Critical Thinking, Low Critical Thinking, Question-Answer Relationship, Teaching Reading.